Instrument platforms for nano liquid chromatography - Šesták, Jozef; Moravcová, Dana; Kahle, Vladislav (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
The history of liquid chromatography started more than a century ago and miniaturization and automation are two leading trends in this field. Nanocolumn liquid chromatography (nano LC) and largely synonymous capillary liquid chromatography (capillary LC) are the most recent results of this process where miniaturization of column dimensions and sorbent particle size play crucial role. Very interesting results achieved in the research of extremely miniaturized LC columns at the end of the last century lacked distinctive raison d'être and only advances in mass spectrometry brought a real breakthrough. Configuration of nano LC-electrospray ionization mass spectrometry (LC-ESI-MS) has become a basic tool in bioanalytical chemistry, especially in proteomics. This review discusses and summarizes past and current trends in the realization of nano liquid chromatography (nano LC) platforms. Special attention is given to the mobile phase delivery under nanoflow rates (isocratic, gradient) and sample injection to the nanocolumn. Available detection techniques applied in nano LC separations are also briefly discussed. We followed up the key themes from the original scientific reports over gradual improvements up to the contemporary commercial solutions.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; mikrochemie; Chromatography, Liquid; Spectrometry, Mass, Electrospray Ionization; nanotechnologie; Nanotechnology; chromatografie kapalinová; Microchemistry